A Randomized Controlled Trial of Long-Term (R)-α-Lipoic Acid Supplementation Promotes Weight Loss in Overweight or Obese Adults without Altering Baseline Elevated Plasma Triglyceride Concentrations. Issue 9 (21st July 2020) - Bobe, Gerd; Michels, Alexander J; Zhang, Wei-Jian; Purnell, Jonathan Q; Woffendin, Clive; Pereira, Cliff; Vita, Joseph A; Thomas, Nicholas O; Traber, Maret G; Frei, Balz; Hagen, Tory M
ABSTRACT: Background: α-Lipoic acid (LA) is a dietary supplement for maintaining energy balance, but well-controlled clinical trials in otherwise healthy, overweight adults using LA supplementation are lacking. Objectives: The primary objective was to evaluate whether LA supplementation decreases elevated plasma triglycerides in overweight or obese adults. Secondary aims examined if LA promotes weight loss and improves oxidative stress and inflammation. Methods: Overweight adults [ n = 81; 57% women; 21–60 y old; BMI (in kg/m 2 ) ≥ 25] with elevated plasma triglycerides ≥100 mg/dL were enrolled in a 24-wk, randomized, double-blind, controlled trial, assigned to either ( R )-α-lipoic acid (R-LA; 600 mg/d) or matching placebo, and advised not to change their diet or physical activity. Linear models were used to evaluate treatment effects from baseline for primary and secondary endpoints. Results: R-LA did not decrease triglyceride concentrations, but individuals on R-LA had a greater reduction in BMI at 24 wk than the placebo group (−0.8; P = 0.04). The effect of R-LA on BMI was correlated to changes in plasma triglycerides ( r = +0.50, P = 0.004). Improvement in body weight was greater at 24 wk in R-LA subgroups than in placebo subgroups. Women and obese participants (BMI ≥ 35) showed greater weight loss (−5.0% and −4.8%, respectively; both P < 0.001) and loss of body fat (−9.4% and −8.6%, respectively; both P < 0.005). Antioxidant gene expression in mononuclear cells at 24 wk was greater in the R-LA group ( Heme oxygenase 1 [HMOX1] : +22%; P = 0.02) than in placebo. Less urinary F2 -isoprostanes (−25%; P = 0.005), blood leukocytes (−10.1%; P = 0.01), blood thrombocytes (−5.1%; P = 0.03), and ICAM-1 (−7.4%; P = 0.04) at 24 wk were also observed in the R-LA group than in placebo. Conclusions: Long-term LA supplementation results in BMI loss, greater antioxidant enzyme synthesis, and less potential for inflammation in overweight adults. Improved cellular bioenergetics is also evident in some individuals given R-LA. This trial was registered at clinicaltrials.gov as NCT00765310.